The ocean of truth a defence of objective theism - Hebblethwaite, Brian 1939-2023 (Cambridge Cambridge University Press, 1988)
This short 1988 book offers an alternative reading of the impact of modernity on Christian faith to that advanced by Don Cupitt in the TV series and book The Sea of Faith. It is a spirited defence of belief in the objective reality of God and in life after death, as opposed to Cupitt's radically interiorised and expressivist conception of religion. As attractive as many may find a denial of the traditional doctrines of the Church in favour of an anti-metaphysical, non-dogmatic expressivist version of Christian faith, Hebblethwaite insists that of greater importance is the question of truth at stake here, and it is on the question of truth that he focusses his attention. After arguing against Cupitt's response to the modern situation, the author tries to show how belief in an objective God is not only possible despite the impact of modern science and historical criticism, but indeed highly plausible.
Preface --1. Christian belief in God -- 2. The ebbing of theistic faith -- 3. The interiorisation of faith -- 4. Theism in the modern world -- 5. The significance of Kant -- 6. The grounds of theistic belief -- 7. The question of truth -- 8. Religions -- theistic and non-theistic -- 9. Life after death -- 10. The Christian Church and objective theism -- Appendix -- Notes -- Select bibliography -- Index
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Cupitt, Don; Truth -- Religious aspects -- Christianity; Truth -- Religious aspects -- Christianity; Theism; Apologetics; Cupitt, Don; Truth ; Religious aspects ; Christianity